2023
DOI: 10.3389/fpubh.2023.1106458
|View full text |Cite
|
Sign up to set email alerts
|

Research hotspots and trends of exercise for sarcopenia: A bibliometric analysis

Abstract: Exercise is an effective method for the prevention and treatment of sarcopenia, which can improve skeletal muscle mass, strength and physical function in individuals with sarcopenia to varying degrees. Moreover, exercise has an important role in improving ability to perform daily activities and quality of life on sarcopenia. In this study, articles and review articles on exercise interventions for sarcopenia from January 2003 to July 2022 were retrieved from the Web of Science core collection. Then, the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Previous studies on DR had shown that the development and validation of deep learning algorithms have made major breakthroughs in the early diagnosis of DR, and were also at the forefront of current DR Research. [49] It showed the importance of deep learning and AI in ophthalmology research, and the integration of multiple disciplines can better promote the development of ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on DR had shown that the development and validation of deep learning algorithms have made major breakthroughs in the early diagnosis of DR, and were also at the forefront of current DR Research. [49] It showed the importance of deep learning and AI in ophthalmology research, and the integration of multiple disciplines can better promote the development of ophthalmology.…”
Section: Discussionmentioning
confidence: 99%